University Sports in Moldova—A Means of Integration for Foreign Students: Challenges and Opportunities in the Context of Migration - Victoria Leșco; Mihail Onoi; Victoria Razmireț; Irina Volcu; Dan Iulian Alexe; Ecaterina Lungu (Societies)
This article aims to analyze to what extent university sports can serve as an effective means of integration for foreign students and the main challenges and opportunities they encounter in the integration process in the context of migration. In this study, “integration” is defined as the process of adapting foreign students to their new academic and social environment, involving the development of interpersonal relationships and active participation in university life. “University sports” refer to the set of physical activities organized within higher education institutions, facilitating student interaction and supporting their psycho-social development. This study aims to analyze the role of university sports activities in facilitating the integration of foreign students. A quantitative analysis was conducted based on data collected through a survey applied to a sample of 134 foreign students enrolled at a university in Moldova. Among them, 25.4% were from Ukraine, 15.7% were from Romania, 17.9% were from Greece, 14.2% were from Russia, and 26.9% were from regions of the Middle East and India. Additionally, 20 interviews with foreign students were conducted to gain a more detailed understanding of their experiences regarding participation in sports competitions. Furthermore, self-assessment questionnaires on well-being were applied. Statistical results showed significant increases in the average scores on all three scales: general well-being (from 2.00 to 2.60, p < 0.001, d = 1.2—large effect), activity (from 1.80 to 2.10, p < 0.05, d = 0.75—moderate effect), and mood (from 2.10 to 2.80, p < 0.001, d = 1.4—large effect). These results highlight that sports activities contribute significantly not only to improving the psychological well-being of foreign students but also to their integration into the university community.